DIAGNOSTIC CHALLENGE AND CONSERVATIVE MANAGEMENT OF CERVICAL PREGNANCY WITH UTEREUS PRESERVATION - Morarcalieva Chochkova, Anita; Nakova, Marina; Velickova, Nevenka; Ismaili, Bashkim; Chochkov, Blazhe (Journal of Morphological Sciences, 2023)
Cervical pregnancy is a rare form of ectopic pregnancy in which the embryo implants in the lining of the endocervical canal. Clinical criteria and ultrasound features, supplemented by rapid assay of serum human chorionic gonadotropin (hCG), make the diagnosis easier and more accurate. Depending on the time of diagnosis and the patient’s condition, management can be conservative or operative Case: We present a rare case of cervical pregnancy with all the diagnostic challenges for making an early diagnosis and choosing the right treatment regimen, which can be life saving for the patients and can reduce the chance of severe hemorrhage necessitating hysterectomy or blood transfusion Early diagnosis, appropriate methotrexate regimen and combination of necessary adjuvant conservative procedures could contribute to successful treatment with preservation of the uterus and future reproductive ability. Keywords : Cervical pregnancy, human chorionic gonadotropin, transvaginal ultrasound, methotrexate, vaginal bleeding. https://doi.org/10.55302/JMS2361093mch